The Effectiveness of Group Cognitive Behavior Therapy on Reduction of Addicts' Depression - M Khaledian; H Kamar Zarin; A Jalalian (Drug Control Headquarters, Research and Education Office, 2014)
Objective: The aim of present research was the study of the effectiveness of group cognitive behavior therapy on reduction of addicts' depression of Ghorveh city. Method: population was included of addicts who were referred to MMT clinics in Ghorveh city in 1392. By random sampling out of 60 referred addicts 24 addicts who were scored highest score on depression selected and divided to two groups randomly. Experimental group was under group C.B.T. for 12 sessions and control group was not under treatment. Beck's depression scale administered among both groups. Results: The results showed experimental group has scored lesser than control group. Conclusion: Group C.B.T. is effective on addicts' depression.